Ultrasonic assessment and finite element modelling of thermo-mechanical damage in mortar - Nogueira,C. L. (2017)
ABSTRACT Experiments were conducted to evaluate degradation of mechanical properties in mortar specimens subjected to thermal and mechanical loading. Ultrasonic pulse velocity was used to assess changes in the microstructure of the specimens due to thermal and mechanical loads applied separately. Both longitudinal and transverse waves were used. At first the specimens were tested in the undamaged stage, and then they were also tested after their exposure to a non-uniform thermal load only, finally, mechanical loading was applied until peak load. A finite element model was used in the dynamic simulation of pulses propagation. Results showed that mortar mix with a larger proportion of coarser aggregates is more sensitive to mechanical loading after exposure to heat than mortar with lesser and smaller aggregate contents. Mortar mix design with less and finer aggregate did not show a reduction in the pulse velocity as intense as the mortar with more coarse aggregate, which indicates a less severe diffuse microcracking.